Respuesta :

Answer:

2(x + 6) = 38

Step-by-step explanation:

First, we choose a variable to represent the unknown number.

1. Let x = the unknown number.

Then, we translate the sentence into an equation using the variable we chose.

"Twice the sum of six and a number is 38."

We do it piece by piece:

"the sum of six and a number":                        x + 6

"Twice the sum of six and a number":              2(x + 6)

"Twice the sum of six and a number is 38.":    2(x + 6) = 38

Now we have an equation that represents the sentence.

2(x + 6) = 38